IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN BUDAYA MELAYU RIAU DI SD NEGERI 183 PEKANBARU - Raudhoh Naratiba; Suroyo; Rhini Fatmasari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
The implementation of local content learning is able to build the nation's character because it pays attention to the characteristics of the environment and local culture as a form of preserving Malay culture and the application of character education to face the currents of globalization at the education level. This study aims to determine the application of character education to students based on local wisdom in the learning process of Riau Malay Culture at SD Negeri 183 Pekanbaru, the supporting factors, inhibiting factors and the efforts of the Mulok BMR teachers in overcoming the obstacles they face. This research is ethnographic research using a qualitative approach. Based on the results in this study, the researchers limited as many as 8 characters that were more considered and implemented properly based on local wisdom in learning Riau Malay Culture at SD Negeri 183 Pekanbaru including religion, honesty, discipline, social care, responsibility, environmental care, independence and respect. Achievement.